Proses Perencanaan Pembangunan dengan Menganalisis Potensi Unggulan Daerah untuk Mendukung Pertumbuhan Ekonomi (Studi Kasus: Kawasan Margonda Kota Depok) - Hazizah, Wahdah; Mulyawan, Rahman; Sutisna, Jajang (Department of Public Administration, Muhammadiyah University of Makassar, 2025)
Development can be defined as a change towards a better state through various efforts that are carried out in a planned manner. Planning and development are inseparable and interrelated. In other words, development requires planning, and this must be realized in development, starting from the regional to the central level. This study aims to examine the government's role in shaping the direction of development, particularly in the Margonda area of Depok City. This area is identified as a promising support area for enhancing the city's economic growth, given its diverse potential and opportunities. The research methodology employed in this study is a case study approach, utilizing a qualitative analysis. The study employs the concept of development planning stages proposed by Lora Ekana Nainggolan, et al. (2023). The results indicate that the government has not fully engaged the community, particularly MSME actors in the Margonda area, in the formulation of programs and policies. However, the local regulations established by the government have comprehensively addressed program implementation, financing of programs or activities to be carried out, and the determination of the vision and mission of development. The vision and mission of development articulated by the Depok City Government are predicated on a future state that is expected to be achieved, rather than on a current or actual state of affairs.